An inexact fuzzy bi-level programming model for energy–traffic system planning under uncertainty: a case study of Urumqi city, China. Issue 8 (3rd August 2017) - Wang, S.; Huang, G. H.; Yao, Y.; Xie, Y. L.; Zhen, J. L.
ABSTRACT: In this study, an inexact fuzzy bi-level programming model was developed for regional energy and traffic system management under uncertainty in Urumqi city, China. The energy system and traffic system are important subsystems of regional areas such as cities. The coordinated management of regional subsystems is a difficult problem for regional management. A bi-level programming model is an appropriate and simple method to describe the coordinated management of regional subsystems. The energy and traffic structure adjustment, clean power generation and pollutant emission–reduction targets are designed to support the construction of an environmentally sustainable city in China. Methods of interval parameter programming and bi-level programming were incorporated into the developed model to tackle uncertainties and reflect the features in the system. The environmental impacts of energy and traffic activities and policies were analysed. The results are valuable for supporting the management or justification of the existing energy and traffic policies and schemes under uncertainty.